(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: There is a high prevalence of coexisting medical conditions in patients with acute stroke; therefore, clinical investigators often need to adjust for comorbidities when assessing the effect of those risk factors on patient outcome. Objective: This study aimed to determines comorbid risk factors in patients with acute stroke. Methodology: A hospital-based case control study was conducted in Shaheed Suhrawardy Medical College Hospital (ShSMCH) and Dhaka Medical College Hospital between January-June 2011. The cases and controls studied consisted of 175 hospitalized patients with stroke (confirmed by computed tomography scan) and 171 matched-age and sex controls that were hospitalized at the study hospital for condition other than stroke. After obtaining written informed consent from the patient or the closest attendant, all the information included to record were age, sex, monthly family income, family size, family history of CVD death, history of hypertension and diabetes mellitus, ECG change, aspirin intake, blood pressure and heart rate, waist and hip circumference and psychosocial factors. The edited data then analyzed by SPSS V. 16. Result: The most predictive independent variables were history of hypertension (OR 4.056), psychosocial stress (OR 4.90) and increased WHR (OR 3.806) were found significant risk factor for developing stroke. Conclusion: Therefore, to recognize comorbid risk factors and to treat them appropriately is the key to establish primary preventive strategies in non-stroke patients or secondary preventive measures to avoid recurrence in stroke victims. Journal of National Institute of Neurosciences Bangladesh, 2016;2(2): 84-88